2020
DOI: 10.1101/2020.04.29.067983
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of 19 antiviral drugs against SARS-CoV-2 Infection

Abstract: The global pandemic of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 or 2019-nCoV) has prompted multiple clinical trials to jumpstart search for anti-SARS-CoV-2 therapies from existing drugs, including those with reported in vitro efficacies as well as those ones that are not known to inhibit SARS-CoV-2, such as ritonavir/lopinavir and favilavir. Here we report that after screening 19 antiviral drugs that are either in clinical trials or with proposed activity against SARS-CoV-2, remdesivir w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 13 publications
2
31
0
1
Order By: Relevance
“…Consistent with our findings, tenofovirdiphosphate has been shown to permanently terminate polymerase extension of nascent RNA when using recombinant RdRp-CoV2 [25]. However, infusion of tenofovir in Vero cell cultures did not inhibit replication of SARS-CoV-2 [26,27], while the use of 3-90 μM of its prodrug TDF yielded a 15-fold reduction of viral genome release [26] . Further, the use of TDF/FTC for treating SARS-CoV-2 infected ferrets led to better clinical scores and lower virus titers in nasal washes compared to a placebo [28].…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with our findings, tenofovirdiphosphate has been shown to permanently terminate polymerase extension of nascent RNA when using recombinant RdRp-CoV2 [25]. However, infusion of tenofovir in Vero cell cultures did not inhibit replication of SARS-CoV-2 [26,27], while the use of 3-90 μM of its prodrug TDF yielded a 15-fold reduction of viral genome release [26] . Further, the use of TDF/FTC for treating SARS-CoV-2 infected ferrets led to better clinical scores and lower virus titers in nasal washes compared to a placebo [28].…”
Section: Discussionsupporting
confidence: 88%
“…A study using polymerase extension assays with a pre-annealed RNA template and primer and a pre-assembled SARS-CoV-2 nsp12-nsp8-nsp7 complex demonstrated that sofosbuvir could block chain extension ( Chien et al., 2020 ). However, a study that evaluated 19 potential anti-CoV drugs demonstrated that sofosbuvir failed to protect cells against SARS-CoV-2-induced cytopathic effects ( Liu et al., 2020 ). Further studies in vitro , in animal models, and in clinical trials are needed to establish whether this, or any drug under investigation, will be effective against CoVs.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Zhu and colleagues [126] demonstrated that arbidol monotherapy was more effective than the use of lopinavir/ritonavir and arbidol. Besides, an in-vitro study performed on lopinavir did not exhibit any direct antiviral activity against SARS-CoV-2 [74] . Regardless of these findings, the administration of lopinavir/ritonavir seems beneficial on SARS-CoV and MERS-CoV only when used at the early stage of infection [127] .…”
Section: Other Pharmacologic Therapiesmentioning
confidence: 90%
“…Chloroquine and HCQ are both known as antimalarial drugs. Clinical studies introduced these two drugs as a possible choice for COVID-19 treatment due to having in-vitro antiviral and anti-inflammatory properties [71] , [72] , [73] , [74] . Several studies suggested that chloroquine could improve the radiological and virological features of COVID-19 [53] .…”
Section: Other Pharmacologic Therapiesmentioning
confidence: 99%